Preparation method of antibacterial wear-resistant waterborne polyurethane coating

By preparing modified polyisocyanate and DOPO-based diol, combined with prepolymerization reaction and chain extension reaction, the existing aqueous polyurethane coatings are easily breeding bacteria and insufficient UV resistance in humid environments, and the antibacterial, UV resistance, flame retardant and wear-resistant coating properties are achieved.

CN119639328AInactive Publication Date: 2025-03-18ANHUI JIAJINGMEI NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411908780.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing water-based polyurethane coatings are prone to bacterial growth in humid or wet environments, have short service life and poor UV resistance.

Method used

Modified polyisocyanate and DOPO-based diol are prepared by using concentrated hydrochloric acid, paraphenylenediamine, sodium nitrite, paraformaldehyde, amino modified nanosilica, adidiisocyanate and other raw materials, and after diazotization coupling reaction, substitution reaction, and mannylene reaction, modified polyisocyanate and DOPO-based diols are prepared, and antibacterial wear-resistant polyurethane coatings are finally prepared through prepolymerization reaction and chain extension reaction.

Benefits of technology

The prepared antibacterial and wear-resistant polyurethane coating has good antibacterial, ultraviolet, flame retardant and wear-resistant properties. It can inhibit bacterial growth in humid environments, extend service life, and show strong stability under ultraviolet light exposure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639328A_ABST
    Figure CN119639328A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane coatings, and discloses a preparation method of an antibacterial wear-resistant waterborne polyurethane coating, which comprises the following steps: taking concentrated hydrochloric acid, p-phenylenediamine, sodium nitrite, paraformaldehyde, amino-modified nano silicon dioxide and hexamethylene diisocyanate as raw materials; the preparation method comprises the following steps: taking 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide as a raw material, carrying out diazotization coupling reaction, substitution reaction, Mannich reaction and addition reaction to prepare modified polyisocyanate, then taking 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and ((2-aminoethyl) azadiyl) dimethanol as raw materials, carrying out substitution reaction to prepare DOPO-based dihydric alcohol, and carrying out reaction to prepare the DOPO-based dihydric alcohol. Finally, the modified polyisocyanate, DOPO-based dihydric alcohol and polyethylene glycol 400 are used as raw materials, an antibacterial wear-resistant polyurethane emulsion is prepared through a prepolymerization reaction and a chain extension reaction, and the prepared polyurethane coating has good antibacterial, anti-ultraviolet, flame-retardant and wear-resistant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane coatings, in particular to a method for preparing an antibacterial and wear-resistant water-based polyurethane coating. Background Art

[0002] Waterborne polyurethane uses water as the dispersion medium. As water is non-toxic, odorless, non-flammable, non-explosive, does not pollute the environment, can significantly reduce product costs, and does not harm the health of operators, it has attracted more and more attention. As a material with excellent performance, good compatibility and environmental friendliness, waterborne polyurethane has been widely used in leather, textile coating and other fields.

[0003] At present, the market mostly uses a combination of halogen flame retardants and water-based polyurethane to provide flame retardant finishing for coated objects, which has the disadvantages of opaque coating, large amount of flame retardant added, and generation of toxic gases and thick smoke during combustion.

[0004] For example, the patent with authorization announcement number CN113088114A discloses a wear-resistant polyurethane coating and a preparation method thereof. The invention uses a polyurethane base resin, acrylate, polyketone resin, nitrocellulose, nano-silicon dioxide, nano-calcium carbonate, additives and solvents, and a polyurethane base resin. The coating composition prepared by the invention is easy to prepare and use, can effectively resist friction, wear, scratch and scrape, and enhance the scratch resistance of the coating surface. However, the coating prepared by this invention is not suitable for humid or moist environments. In such environments, bacteria are easily bred, shortening the service life, and the anti-ultraviolet performance is poor. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing an antibacterial and wear-resistant water-based polyurethane coating, and the prepared polyurethane coating has good antibacterial, anti-ultraviolet, flame retardant and wear-resistant properties.

[0007] (II) Technical solution

[0008] A method for preparing an antibacterial and wear-resistant waterborne polyurethane coating comprises the following steps: adding a polyurethane emulsion into a stirrer, stirring at high speed for 15 to 30 minutes, adding a cosolvent ethanol butyl ether, a slip agent (DC-56), a leveling agent (H-140) and a defoamer (W-0506), mixing them evenly, adding a diluent (ZP-110), stirring at high speed for 15 to 30 minutes, and preparing the antibacterial and wear-resistant polyurethane coating.

[0009] Preferably, the polyurethane emulsion preparation method is:

[0010] (1) Add 37% concentrated hydrochloric acid to deionized water, add 1,3,5-triaminobenzene, cool to -5 to 0°C, stir and react for 30-50 minutes, then drop an aqueous solution of sodium nitrite, add dropwise, react for 50-90 minutes, remove impurities, filter, add deionized water, then add p-methylphenol, sodium hydroxide, and anhydrous sodium carbonate, stir and mix, react for 2-4 hours, filter, wash with hot deionized water and ethanol, and dry to obtain intermediate 1;

[0011] (2) Add paraformaldehyde to chloroform solvent, add calcium hydride, heat to 20-30°C, react for 20-40 minutes, then heat to 50-70°C, add amino-modified nano-silica, heat to 75-85°C, add intermediate 1, react for 50-90 minutes, filter, column chromatography, and low-pressure distillation to obtain intermediate 2;

[0012] (3) Add intermediate 2, hexamethylene diisocyanate, to butyl acetate solvent, stir evenly, add catalyst dibutyltin dilaurate (DBTDL), heat to 70-90° C., react for 2-4 hours, cool, and distill at low pressure to obtain modified polyisocyanate;

[0013] (4) Under a nitrogen atmosphere, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), triethylamine (TEA), and ((2-aminoethyl)azadiyl)dimethanol are added to a dichloromethane solvent, the temperature is lowered to -10 to 0°C, carbon tetrachloride is added, the temperature is raised to 5-15°C, and after the addition is complete, the temperature is raised to 20-30°C, the reaction is carried out for 10-14 hours, and the mixture is filtered, washed with deionized water, and dried to obtain a DOPO-based diol;

[0014] (5) Under nitrogen atmosphere, modified polyisocyanate, polyethylene glycol 400 (PEG400), and DOPO-based diol are added to a three-necked flask, stirred and mixed evenly, heated to 80-90°C, reacted for 2-4h, cooled to 35-55°C, dimethylol propionic acid (DMPA) and 1,4-butanediol (BDO) are added, heated to 70-90°C, reacted for 30-90min, cooled to 35-50°C, catalysts dibutyltin dilaurate and stannous octoate are added, heated to 60-80°C, reacted for 3-5h, the reaction is completed, cooled to 30-50°C, neutralized with triethylamine, emulsified with deionized water, chain extended with ethylenediamine (EDA), and distilled under reduced pressure to obtain a polyurethane emulsion.

[0015] Preferably, the ethanol butyl ether accounts for 3% to 10% of the mass of the polyurethane emulsion, the slip agent accounts for 0.2% to 0.5% of the mass of the polyurethane emulsion, the defoamer accounts for 0.6% to 1% of the mass of the polyurethane emulsion, the leveling agent accounts for 0.3% to 0.5% of the mass of the polyurethane emulsion, and the diluent accounts for 15% to 20% of the mass of the polyurethane emulsion.

[0016] Preferably, in step (1), the molar ratio of concentrated hydrochloric acid, 1,3,5-triaminobenzene, sodium nitrite, deionized water, p-methylphenol, sodium hydroxide and anhydrous sodium carbonate is 35.5-36.5:1:4-5:160-170:2.5-3.5:2.5-3.5:8-10.

[0017] Preferably, in step (2), the molar ratio of intermediate 1, calcium hydride, paraformaldehyde and amino-modified nano-silica is 1:4-5:5.5-7:3-3.5.

[0018] Preferably, in step (3), the molar ratio of intermediate 2, DBDTDL and hexamethylene diisocyanate is 1:0.0005-0.0015:3-3.5.

[0019] Preferably, in step (4), the molar ratio of DOPO, TEA, ((2-aminoethyl)azadiyl)dimethanol and carbon tetrachloride is 1:0.8-1.2:0.35-0.45:0.8-1.2.

[0020] Preferably, in step (5), the molar mass ratio of DOPO-based diol, modified polyisocyanate, PEG400, DMPA, BDO, dibutyltin dilaurate, stannous octoate, and ethylenediamine is 1:9-9.5:1.8-2.2:0.8-1.2:1.3-1.7:0.07-0.1:0.12-0.16:1.5-2.

[0021] (III) Beneficial technical effects

[0022] The invention uses concentrated hydrochloric acid, p-phenylenediamine, sodium nitrite, polyformaldehyde, amino-modified nano-silica and hexamethylene diisocyanate as raw materials, and prepares modified polyisocyanate through diazotization coupling reaction, substitution reaction and Manniene reaction. Then, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and ((2-aminoethyl)azadiyl)dimethanol are used as raw materials, and DOPO-based diol is prepared through substitution reaction. Finally, the modified polyisocyanate, DOPO-based diol and polyethylene glycol 400 are used as raw materials, and prepolymerization reaction and chain extension reaction are carried out to prepare antibacterial and wear-resistant polyurethane coating.

[0023] The antibacterial and wear-resistant polyurethane coating prepared by the present invention contains quaternary ammonium salt groups, which have positive charges and can be adsorbed on the surface of microorganisms to form micelles and gradually penetrate into the lipid layer and protein layer of the cytoplasm, thereby changing the permeability of the cell membrane and causing the cell contents to extravasate, leading to the death of the microorganisms. At the same time, the proteins are coagulated, the enzymes and structural proteins are denatured, the metabolism of the microorganisms is destroyed, and the microorganisms are killed, thereby improving the antibacterial property of the coating.

[0024] The antibacterial and wear-resistant polyurethane coating prepared by the present invention contains nano-silicon dioxide, and a network structure is formed between the nano-silicon dioxide and the organic matrix, which can change the stress concentration of the polyurethane coating. When the material is impacted, it causes more yield deformation of the surrounding matrix, increases the crack propagation resistance of the matrix, and enhances the toughness. At the same time, when the coating is cured, the polymer chain links and covalent bonds themselves shrink, and the addition of the non-shrinking component nano-silicon dioxide can fill the gaps generated by the shrinkage of the organic component, thereby achieving the effect of reducing the internal stress of the material, and thus having better wear resistance.

[0025] The antibacterial and wear-resistant polyurethane coating prepared by the present invention contains an azo group, which has the characteristics of photochromism and photoinduced cis-trans isomerization, and the azo group has an obvious absorption peak in the ultraviolet region (especially between 200-400nm). The reason is that the π electrons in the azo group are prone to transition under the irradiation of ultraviolet light, from a lower energy level to a higher energy level, and this transition absorbs ultraviolet light and reduces the penetration of ultraviolet light, thereby achieving an anti-ultraviolet effect. Introducing it into the coating can improve the anti-ultraviolet performance of the coating.

[0026] The antibacterial wear-resistant polyurethane coating prepared by the present invention contains phosphorus, nitrogen and silicon elements. The nitrogen element will decompose and produce a large amount of non-combustible gas during combustion, and the non-combustible gas can dilute the concentration of oxygen around the coating. The silicon element can migrate to the outside of the material during combustion, and the Si-O bond in its molecule will be converted into a Si-C bond. The generated white combustion residue and carbide form a covering layer on the surface of the coating to prevent the escape of combustion volatiles and prevent oxygen from contacting the base material, thereby improving the flame retardant performance of the coating. The phosphorus element will release a large amount of gas or high-density steam when heated or burned, which can dilute the oxygen and gaseous combustibles in the air, and reduce the surface temperature of the combustion object, causing the combustion to stop. At the same time, the phosphorus component in the structure of the present invention will capture the H· and ·OH free radicals formed during the combustion process, thereby producing a good quenching effect and carbonization effect, and the formation of the carbon layer reduces the release of volatiles. The antibacterial wear-resistant polyurethane coating prepared by the present invention has good wear resistance, antibacterial performance, flame retardant performance and anti-ultraviolet performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the synthetic route of intermediate 2;

[0028] Figure 2 It is a modified polyisocyanate synthesis route;

[0029] Figure 3 It is a synthetic route for DOPO-based diols. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Preparation method of amino-modified nano-silica:

[0032] Add 1 mL of 3-aminopropyltrimethoxysilane and 3.6 mL of anhydrous ethanol into 0.4 mL of distilled water to prepare a silane solution, let it stand for 10 minutes, add 12.5 mL of anhydrous ethanol and 1.0 g of nano-silica into 0.21 mL of the silane solution, ultrasonically disperse, mechanically stir, heat to 78°C, react for 2 hours, filter, dry, and grind to obtain amino-modified nano-silica.

[0033] Example 1

[0034] (1) 3.55 mol of 37% concentrated hydrochloric acid was added to 150 ml of deionized water, and 0.1 mol of 1,3,5-triaminobenzene was added. The temperature was lowered to -5°C, and the mixture was stirred for 50 min. Then, 0.5 mol of an aqueous solution of sodium nitrite was added dropwise. After the addition was complete, the mixture was reacted for 60 min. After the reaction was completed, impurities were removed, the mixture was filtered, and 16 mol of deionized water, 0.3 mol of p-methylphenol, 0.25 mol of sodium hydroxide, and 1 mol of anhydrous sodium carbonate were added. The mixture was stirred and mixed uniformly, and the mixture was reacted for 3 h. After the reaction was completed, the mixture was filtered, washed with hot deionized water and ethanol, and dried to obtain intermediate 1.

[0035] (2) Add 0.7 mol of polyformaldehyde to 100 ml of chloroform solvent, add 0.45 mol of calcium hydride, heat to 30°C, react for 20 min, then heat to 60°C, add 0.35 mol of amino-modified nano-silica, heat to 85°C, add 0.1 mol of intermediate 1, react for 90 min, filter, separate by column chromatography, and distill at low pressure to obtain intermediate 2.

[0036] (3) 0.1 mol of intermediate 2 and 0.35 mol of hexamethylene diisocyanate were added to 200 ml of butyl acetate solvent, stirred evenly, 0.05 mmol of catalyst dibutyltin dilaurate (DBTDL) was added, the temperature was raised to 90° C., the reaction was carried out for 2 h, the temperature was lowered, and low-pressure distillation was performed to obtain modified polyisocyanate.

[0037] (4) Under nitrogen atmosphere, 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 0.08 mol of triethylamine (TEA), and 0.045 mol of ((2-aminoethyl)azadiyl)dimethanol were added to 100 ml of dichloromethane solvent, cooled to -10°C, 0.12 mol of carbon tetrachloride was added, and the temperature was raised to 15°C. After the addition was completed, the temperature was raised to 20°C, and the reaction was carried out for 14 hours. The mixture was filtered, washed with deionized water, and dried to obtain DOPO-based diol.

[0038] (5) Under nitrogen atmosphere, 0.95 mol of modified polyisocyanate, 0.2 mol of polyethylene glycol 400 (PEG400), and 0.1 mol of DOPO-based diol were added to a three-necked flask, stirred and mixed evenly, heated to 85°C, reacted for 2 h, cooled to 55°C, 0.08 mol of dihydroxymethylpropionic acid (DMPA) and 0.15 mol of 1,4-butanediol (BDO) were added, heated to 70°C, reacted for 90 min, cooled to 50°C, 0.01 mol of catalyst dibutyltin dilaurate and 0.015 mol of stannous octoate were added, heated to 80°C, reacted for 3 h, the reaction was completed, cooled to 30°C, neutralized with triethylamine, emulsified with deionized water, chain extended with 0.15 mol of ethylenediamine (EDA), and distilled under reduced pressure to obtain a polyurethane emulsion.

[0039] (6) Add 10 parts by weight of the polyurethane emulsion into a stirrer and stir at high speed for 30 minutes, add 0.03 parts of the cosolvent ethanol butyl ether, 0.05 parts by weight of the slip agent (DC56), 0.03 parts by weight of the leveling agent (H-140) and 0.06 parts by weight of the defoaming agent (W-0506), mix well, add 1.5 parts by weight of the diluent (ZP-110), stir at high speed for 15 minutes, and prepare an antibacterial and wear-resistant polyurethane coating.

[0040] Example 2

[0041] (1) 3.65 mol of 37% concentrated hydrochloric acid was added to 150 ml of deionized water, and 0.1 mol of 1,3,5-triaminobenzene was added. The temperature was lowered to 0°C and stirred for 30 min. Then, 0.4 mol of an aqueous solution of sodium nitrite was added dropwise. After the addition was complete, the mixture was reacted for 50 min. After the reaction was completed, impurities were removed and the mixture was filtered. 17 mol of deionized water, 0.35 mol of p-methylphenol, 0.3 mol of sodium hydroxide and 0.8 mol of anhydrous sodium carbonate were added. The mixture was stirred and mixed evenly and reacted for 4 h. After the reaction was completed, the mixture was filtered, washed with hot deionized water and ethanol, and dried to obtain intermediate 1.

[0042] (2) Add 0.5 mol of polyformaldehyde to 100 ml of chloroform solvent, add 0.4 mol of calcium hydride, heat to 30°C, react for 20 min, then heat to 70°C, add 0.3 mol of amino-modified nano-silica, heat to 75°C, add 0.1 mol of intermediate 1, react for 30 min, filter, separate by column chromatography, and distill at low pressure to obtain intermediate 2.

[0043] (3) 0.1 mol of intermediate 2 and 0.3 mol of hexamethylene diisocyanate were added to 200 ml of butyl acetate solvent, stirred evenly, 0.15 mmol of DBTDL as a catalyst was added, the temperature was raised to 70° C., the reaction was carried out for 4 h, the temperature was lowered, and low-pressure distillation was performed to obtain a modified polyisocyanate.

[0044] (4) Under nitrogen atmosphere, 0.1 mol of DOPO, 0.12 mol of TEA, and 0.035 mol of ((2-aminoethyl)azadiyl)dimethanol were added to 100 ml of dichloromethane solvent, cooled to 0°C, carbon tetrachloride was added, and the temperature was raised to 5°C. After the addition was complete, the temperature was raised to 30°C, and the reaction was carried out for 10 hours. The mixture was filtered, washed with deionized water, and dried to obtain DOPO-based diol.

[0045] (5) Under nitrogen atmosphere, 0.9 mol of modified polyisocyanate, 0.22 mol of PEG400 and 0.1 mol of DOPO-based diol were added to a three-necked flask, stirred and mixed evenly, heated to 90°C, reacted for 4 h, cooled to 35°C, 0.12 mol of DMPA and 0.13 mol of BDO were added, heated to 90°C, reacted for 30 min, cooled to 35°C, 0.007 mol of catalyst dibutyltin dilaurate and 0.012 mol of stannous octoate were added, heated to 80°C, reacted for 3 h, the reaction was completed, cooled to 50°C, neutralized with triethylamine, emulsified with deionized water, chain extended with 0.2 mol of EDA, and distilled under reduced pressure to obtain a polyurethane emulsion.

[0046] (6) Add 10 parts by weight of the polyurethane emulsion into a stirrer and stir at high speed for 15 minutes, add 1 part by weight of the cosolvent ethanol butyl ether, 0.02 parts by weight of the slip agent, 0.05 parts by weight of the leveling agent and 0.1 parts by weight of the defoaming agent, mix well, add the diluent, stir at high speed for 15-30 minutes, and prepare an antibacterial and wear-resistant polyurethane coating.

[0047] Example 3

[0048] (1) 3.6 mol of 37% concentrated hydrochloric acid was added to 150 ml of deionized water, and 0.1 mol of 1,3,5-triaminobenzene was added. The temperature was lowered to -2°C, and the mixture was stirred for 40 min. Then, 0.45 mol of an aqueous solution of sodium nitrite was added dropwise. After the addition was complete, the mixture was reacted for 90 min. After the reaction was completed, impurities were removed, the mixture was filtered, and 16.5 mol of deionized water, 0.25 mol of p-methylphenol, 0.35 mol of sodium hydroxide, and 0.9 mol of anhydrous sodium carbonate were added. The mixture was stirred and mixed evenly, and the mixture was reacted for 2 h. After the reaction was completed, the mixture was filtered, washed with hot deionized water and ethanol, and dried to obtain intermediate 1.

[0049] (2) Add 0.6 mol of polyformaldehyde to 100 ml of chloroform solvent, add 0.5 mol of calcium hydride, heat to 20°C, react for 40 min, then heat to 50°C, add 0.31 mol of amino-modified nano-silica, heat to 80°C, add 0.1 mol of intermediate 1, react for 60 min, filter, separate by column chromatography, and distill at low pressure to obtain intermediate 2.

[0050] (3) 0.1 mol of intermediate 2 and 0.31 mol of hexamethylene diisocyanate were added to 200 ml of butyl acetate solvent, stirred evenly, 0.1 mmol of DBTDL as a catalyst was added, the temperature was raised to 80° C., reacted for 3 h, cooled, and distilled under low pressure to obtain modified polyisocyanate.

[0051] (4) Under nitrogen atmosphere, 0.1 mol of DOPO, 0.1 mol of TEA, and 0.04 mol of ((2-aminoethyl)azadiyl)dimethanol were added to 100 ml of dichloromethane solvent, cooled to -8°C, carbon tetrachloride was added, and the temperature was raised to 10°C. After the addition was complete, the temperature was raised to 25°C, and the reaction was carried out for 12 hours. The mixture was filtered, washed with deionized water, and dried to obtain DOPO-based diol.

[0052] (5) Under nitrogen atmosphere, 0.92 mol of modified polyisocyanate, 0.18 mol of PEG400 and 0.1 mol of DOPO-based diol were added to a three-necked flask, stirred and mixed evenly, heated to 85°C, reacted for 3 h, cooled to 40°C, 0.1 mol of DMPA and 0.17 mol of BDO were added, heated to 80°C, reacted for 60 min, cooled to 40°C, 0.008 mol of dibutyltin dilaurate and 0.016 mol of stannous octoate as catalyst were added, heated to 70°C, reacted for 4 h, the reaction was completed, cooled to 40°C, neutralized with triethylamine, emulsified with deionized water, chain extended with 1.7 mol of EDA, and distilled under reduced pressure to obtain a polyurethane emulsion.

[0053] (6) Add 10 parts by weight of the polyurethane emulsion into a stirrer and stir at high speed for 25 minutes, add 0.5 parts by weight of the cosolvent ethanol butyl ether, 0.03 parts by weight of the slip agent, 0.04 parts by weight of the leveling agent, and 0.08 parts by weight of the defoaming agent, mix well, then add 1.8 parts by weight of the diluent and stir at high speed for 20 minutes to prepare an antibacterial and wear-resistant polyurethane coating.

[0054] Example 4

[0055] The difference between this embodiment and embodiment 1 is that the amount of each raw material used in step (5) embodiment 4 is twice that of embodiment 1.

[0056] Example 5

[0057] The difference between this embodiment and embodiment 1 is that the amount of each raw material used in step (5) of embodiment 5 is four times that of embodiment 1.

[0058] Example 6

[0059] The difference between this embodiment and embodiment 1 is that the amount of each raw material used in step (5) embodiment 6 is six times that of embodiment 1.

[0060] Comparative Example 1

[0061] The difference between this comparative example and Example 1 is that in step (5) of Comparative Example 1, the modified polyisocyanate is replaced by isophorone diisocyanate.

[0062] Comparative Example 2

[0063] The difference between this comparative example and Example 1 is that in step (5) of Comparative Example 2, no DOPO-based diol is added.

[0064] Preparation of paint film

[0065] According to the national standard GB1727-92, the paint film was prepared by brushing. The substrate was tinplate, which was sanded and derusted and degreased in advance. The coatings of Examples 1-6 and Comparative Examples 1-2 were brushed with emulsions. The dry film thickness was 40 μm. When brushing, the emulsions were quickly and evenly brushed in the horizontal and vertical directions to prevent the emulsions from overflowing and leaving no blank space on the substrate. The paint films of Examples 1-6 and Comparative Examples 1-2 were placed in a constant temperature (30°C) and constant humidity (relative humidity 40%) room for 7 days before the paint film performance test was carried out.

[0066] Wear resistance test

[0067] According to the national standard GB / T178-2006, the wear resistance of the paint film was tested using a paint film abrasion tester (BGD-523).

[0068] Steps: A pair of weights of 750 g each are loaded on the paint films of Examples 1-6 and Comparative Examples 1-2, and the CS-10 grinding wheel is pre-grinded for 50 r with sandpaper, and then the paint film surface is polished with a pair of CS-10 grinding wheels at 60 r / min, and the dust is removed with a vacuum cleaner. After the instrument is operated for 500 r, the surface is cleaned, and the mass change before and after polishing is recorded. The mass change data is used as the wear resistance data of the paint film.

[0069] Paint film pencil hardness test

[0070] According to the national standard GB / T6739-2006, the pencil hardness of the paint film was tested using a trolley-type pencil hardness tester (BGD-506 / 2).

[0071] Steps: Grind the tip of the pencil with sandpaper, rotate it to grind it flat, insert it into the hardness tester with both ends placed horizontally at a 45° angle until it touches the surface of the paint film, remove the pad at the front end of the hardness tester, push the trolley forward 7-10mm at a speed of 0.5mm / s-1mm / s, and visually check and feel whether there are scratches or cuts on the surface of the paint film. Test three times in parallel at different positions. The hardest pencil model that does not cause scratches on the surface of the paint film is taken as the hardness of the paint film.

[0072] Paint film impact resistance test

[0073] According to the national standard GB / T 1732-1993, a tubular paint film impactor (BGD-302) is used to test the impact resistance of the paint film.

[0074] Steps: Prepare paint films with a dry film thickness of about 40 μm in Examples 1-6 and Comparative Examples 1-2 respectively, put them into the bottom of a tubular impactor, and allow a 1 kg hammer to slide freely from different heights in the tube to impact the iron sheet. The impact point should be greater than 1.5 cm away from the edge of the test plate or other test points. Each example or comparative example is subjected to three positive or negative impacts, and the highest impact height corresponding to no cracks or peeling is used as an impact resistance indicator of the paint film.

[0075] Table 1: Test data of various embodiments and comparative examples

[0076]

[0077]

[0078] As can be seen from Table 1, the wear resistance, impact resistance and pencil hardness of Comparative Example 1 are relatively poor compared with other embodiments and comparative examples. The reason is that Examples 1-6 and Comparative Example 2 all contain nano-silicon dioxide, and nano-silicon dioxide can form a network structure with the organic matrix, thereby changing the stress concentration of the polyurethane coating, causing more yield deformation of the surrounding matrix when the material is impacted, increasing the crack propagation resistance of the matrix, and enhancing the toughness. At the same time, when the coating is cured, the polymer chain links and covalent bonds themselves shrink, and the addition of the non-shrinking component nano-silicon dioxide can fill the gaps caused by the shrinkage of the organic component, thereby achieving the effect of reducing the internal stress of the material, and thus having better wear resistance.

[0079] Antimicrobial testing

[0080] The antibacterial test was carried out according to the AATCC 100-2012 immersion method. Escherichia coli and Aspergillus niger were selected as test bacteria. The same mass of bacterial solution was evenly dripped on the paint films of Examples 1-6 and Comparative Examples 1-2, and a blank control group (Sankeshu paint) was set up. After culturing for 24 hours, the bacterial count reduction rate, i.e., the antibacterial rate, was calculated.

[0081] R(%)=[(BA) / B]×100

[0082] Where: R------bacteria reduction rate, %;

[0083] A------The number of bacteria in the paint film sample after contact culture;

[0084] B-------The number of bacteria in the paint film sample that has not been cultured.

[0085] Table 2: Antibacterial test results of various embodiments and comparative examples

[0086] A(cfu / ml) B (cfu / ml) R(%) Example 1 <![CDATA[1.46×10 3 ]]> <![CDATA[9.10×10 3 ]]> 84 Example 2 <![CDATA[1.85×10 3 ]]> <![CDATA[9.25×10 3 ]]> 80 Example 3 <![CDATA[0.98×10 3 ]]> <![CDATA[8.94×10 3 ]]> 89 Example 4 <![CDATA[1.32×10 3 ]]> <![CDATA[8.83×10 3 ]]> 85 Example 5 <![CDATA[1.23×10 3 ]]> <![CDATA[9.46×10 3 ]]> 87 Example 6 <![CDATA[1.38×10 3 ]]> <![CDATA[9.83×10 3 ]]> 86 Comparative Example 1 <![CDATA[1.72×10 3 ]]> <![CDATA[9.58×10 3 ]]> 82 Comparative Example 2 <![CDATA[1.73×10 3 ]]> <![CDATA[9.10×10 3 ]]> 81 Blank control group <![CDATA[8.33×10 3 ]]> <![CDATA[9.25×10 3 ]]> 10

[0087] As can be seen from Table 2, the antibacterial rates of Examples 1-6 and Comparative Examples 1-2 are both higher than 80%, while the blank control group is a commercially available Sankeshu paint with an antibacterial rate of 10%, which is relatively poor in antibacterial properties. Therefore, Examples 1-6 and Comparative Examples 1-2 have certain antibacterial properties. The reason is that both Examples 1-6 and Comparative Examples 1-2 contain quaternary ammonium salt groups, which have a positive charge and can be adsorbed on the surface of microorganisms to form micelles and gradually penetrate into the lipid layer and protein layer of the cytoplasm, thereby changing the permeability of the cell membrane, causing the cell contents to extravasate, leading to the death of the microorganisms, and at the same time coagulating proteins, denaturing enzymes and structural proteins, destroying the metabolism of microorganisms, and killing microorganisms, thereby improving the antibacterial properties of the coating.

[0088] UV resistance detection

[0089] Take 3 samples of each of Examples 1-6 and Comparative Examples 1-2, and place the samples in a QUV accelerated aging tester according to the test method specified in Q / JLY J7110279. 2 / nm) is 0.76, the UV wavelength is 340nm, the temperature is 60℃, the test time is 1200h, and after the test, the appearance is detected, the color difference is evaluated, and the gloss and adhesion are measured.

[0090] Glossiness test

[0091] The glossiness test method manufactured by Three Enshi Technology Co., Ltd. was adopted, and the glossiness tester was used for testing. The glossiness of the paint film at 60° was measured with reference to GB1743-1979 "Paint Film Gloss Determination Method".

[0092] Color difference detection

[0093] The DS-600 spectrophotometer was used to test and record the color difference of the samples before and after light aging.

[0094] Table 3: Anti-ultraviolet detection test results of various embodiments and comparative examples

[0095]

[0096] As shown in Table 3, the paint film surface of Comparative Example 1 is uneven, so the refractive index of light decreases. After calculation, the gloss loss rate of Comparative Example 1 is 12.7%, while the gloss loss rate of other embodiments and comparative examples is 5.1% on average. At the same time, by comparing the color difference ΔE, it can be found that the anti-ultraviolet aging ability of Comparative Example 1 is weak. This is because other embodiments and comparative examples contain azo groups, which have the characteristics of photochromism and photoinduced cis-trans isomerization, and the azo group has an obvious absorption peak in the ultraviolet region (especially between 200-400nm). The reason is that the π electrons in the azo group are prone to transition under the irradiation of ultraviolet light, from a lower energy level to a higher energy level. This transition absorbs ultraviolet light and reduces the penetration of ultraviolet light, thereby achieving an anti-ultraviolet effect. Introducing it into the coating can improve the anti-ultraviolet performance of the coating.

[0097] Flame retardant performance testing

[0098] The paint films of Examples 1-6 and Comparative Examples 1-2 were prepared into a size of 100 mm×6.5 mm×3 mm, and LOI tests were performed using an oxygen index meter according to ASTM D2863 standard.

[0099] Table 4: LOI test results of various embodiments and comparative examples

[0100]

[0101]

[0102] As shown in Table 4, the oxygen index of Comparative Example 2 is lower than that of other embodiments and comparative examples. The reason is that Examples 1-6 contain phosphorus, nitrogen, and silicon elements. The nitrogen element will decompose and produce a large amount of non-combustible gas when burning. The non-combustible gas can dilute the concentration of oxygen around the coating. The silicon element can migrate to the outside of the material when burning, and the Si-O bond in its molecule will be converted into Si-C bond. The generated white combustion residue and carbide form a covering layer on the surface of the coating, preventing the combustion volatiles from escaping and preventing oxygen from contacting the base material, thereby improving the flame retardant performance of the coating. The phosphorus element will release carbon dioxide when heated or burned. Releasing a large amount of gas or high-density steam can dilute the oxygen and gaseous combustibles in the air and reduce the surface temperature of the burning material, causing the combustion to stop. The reason why the oxygen index of Comparative Example 1 is higher than that of Comparative Example 2 is that the phosphorus component in the structure of Comparative Example 1 will capture the H· and ·OH free radicals formed during the combustion process, thereby producing a better quenching effect and carbonization effect. The formation of the carbon layer reduces the release of volatiles. At the same time, the carbonized layer can isolate the fire source and the paint film, limit the volatilization of combustible gases, prevent the generation of new free radicals, reduce the combustion rate, and reduce the amount of heat release, thereby achieving a flame retardant effect.

Claims

1. A method for preparing an antibacterial and wear-resistant waterborne polyurethane coating, characterized in that: The preparation method comprises the following steps: adding the modified polyurethane emulsion into a stirrer, stirring at high speed for 15-30 minutes, adding a cosolvent ethanol butyl ether, a slip agent (DC-56), a leveling agent (H-140) and a defoaming agent (W-0506), mixing them evenly, adding a diluent (ZP-110), stirring at high speed for 15-30 minutes, and preparing an antibacterial and wear-resistant polyurethane coating.

2. The method for preparing the antibacterial and wear-resistant waterborne polyurethane coating according to claim 1, characterized in that: The modified polyurethane emulsion preparation method is: (1) Add 37% concentrated hydrochloric acid to deionized water, add 1,3,5-triaminobenzene, cool to -5 to 0°C, stir and react for 30-50 minutes, then drop an aqueous solution of sodium nitrite, add dropwise, react for 50-90 minutes, remove impurities after the reaction is complete, filter, add deionized water, then add p-methylphenol, sodium hydroxide, and anhydrous sodium carbonate, stir and mix evenly, react for 2-4 hours, filter, wash with hot deionized water and ethanol, and dry to obtain intermediate 1; (2) Add paraformaldehyde to chloroform solvent, add calcium hydride, heat to 20-30°C, react for 20-40 minutes, then heat to 50-70°C, add amino-modified nano-silica, heat to 75-85°C, add intermediate 1, react for 50-90 minutes, filter, separate by column chromatography, and distill at low pressure to obtain intermediate 2; (3) Add intermediate 2, hexamethylene diisocyanate, to butyl acetate solvent, stir evenly, add catalyst dibutyltin dilaurate (DBTDL), heat to 70-90° C., react for 2-4 hours, cool, and distill at low pressure to obtain modified polyisocyanate; (4) Under a nitrogen atmosphere, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), triethylamine (TEA), and ((2-aminoethyl)azadiyl)dimethanol are added to a dichloromethane solvent, the temperature is lowered to -10 to 0°C, carbon tetrachloride is added, the temperature is raised to 5-15°C, and after the addition is complete, the temperature is raised to 20-30°C, the reaction is carried out for 10-14 hours, and the mixture is filtered, washed with deionized water, and dried to obtain a DOPO-based diol; (5) Under nitrogen atmosphere, the modified polyisocyanate, polyethylene glycol 400 (PEG400), and DOPO-based diol are added to a three-necked flask, stirred and mixed evenly, heated to 80-90°C, reacted for 2-4h, cooled to 35-55°C, dimethylol propionic acid (DMPA) and 1,4-butanediol (BDO) are added, heated to 70-90°C, reacted for 30-90min, cooled to 35-50°C, catalysts dibutyltin dilaurate and stannous octoate are added, heated to 60-80°C, reacted for 3-5h, the reaction is completed, cooled to 30-50°C, neutralized with triethylamine, emulsified with deionized water, chain extended with ethylenediamine (EDA), and distilled under reduced pressure to obtain a modified polyurethane emulsion.

3. The method for preparing the antibacterial and wear-resistant waterborne polyurethane coating according to claim 1, characterized in that: The ethanol butyl ether accounts for 3% to 10% of the mass of the polyurethane emulsion, the slip agent accounts for 0.2% to 0.5% of the mass of the polyurethane emulsion, the defoamer accounts for 0.6% to 1% of the mass of the polyurethane emulsion, the leveling agent accounts for 0.3% to 0.5% of the mass of the polyurethane emulsion, and the diluent accounts for 15% to 20% of the mass of the polyurethane emulsion.

4. The method for preparing the antibacterial and wear-resistant waterborne polyurethane coating according to claim 2, characterized in that: In the step (1), the molar ratio of concentrated hydrochloric acid, 1,3,5-triaminobenzene, sodium nitrite, deionized water, p-methylphenol, sodium hydroxide and anhydrous sodium carbonate is 35.5-36.5:1:4-5:160-170:2.5-3.5:2.5-3.5:8-10.

5. The method for preparing the antibacterial and wear-resistant waterborne polyurethane coating according to claim 2, characterized in that: In the step (2), the molar ratio of the intermediate 1, calcium hydride, paraformaldehyde and amino-modified nano-silica is 1:4-5:5.5-7:3-3.

5.

6. The method for preparing the antibacterial and wear-resistant waterborne polyurethane coating according to claim 2, characterized in that: In the step (3), the molar ratio of the intermediate 2, DBDTDL and hexamethylene diisocyanate is 1:0.0005-0.0015:3-3.

5.

7. The method for preparing the antibacterial and wear-resistant waterborne polyurethane coating according to claim 2, characterized in that: In the step (4), the molar ratio of DOPO, TEA, ((2-aminoethyl)azadiyl)dimethanol and carbon tetrachloride is 1:0.8-1.2:0.35-0.45:0.8-1.

2.

8. The method for preparing the antibacterial and wear-resistant waterborne polyurethane coating according to claim 2, characterized in that: In the step (5), the molar mass ratio of DOPO-based diol, modified polyisocyanate, PEG400, DMPA, BDO, dibutyltin dilaurate, stannous octoate, and ethylenediamine is 1:9-9.5:1.8-2.2:0.8-1.2:1.3-1.7:0.07-0.1:0.12-0.16:1.5-2.

Citation Information

Patent Citations

  • Wear-resistant polyurethane coating and preparation method thereof

    CN113088114A

  • Flame-retardant antibacterial wood lacquer coating and preparation method thereof

    CN117625030A

  • Preparation method of high-temperature-resistant epoxy polyurethane coating

    CN118222170A

  • Preparation method of flame-retardant modified waterborne polyurethane coating

    CN118995031A

  • Preparation method of impact-resistant high-strength polyurethane coating and application of impact-resistant high-strength polyurethane coating in stone

    CN119060624A

Cited By

  • Heat-resistant polyurethane composition for synthetic leather and preparation method of heat-resistant polyurethane composition

    CN121203121A

  • A heat-resistant polyurethane composition for synthetic leather and its preparation method

    CN121203121B